Optimasi Penugasan Kurir untuk Meminimumkan Biaya Distribusi Menggunakan Metode Hungaria - Nerly Khairani; Dear Sevtia Karo Karo; Herdita Ginting; Juanda Arif Darmawan Damanik (STKIP Subang, 2026)
This study aims to optimize courier assignment at a distribution company in Medan City using the Hungarian Method to minimize daily operational distribution costs. The courier assignment problem is represented as a 4×4 cost matrix containing the distribution costs of four couriers (K1–K4) to four zones: Medan Kota, Medan Baru, Medan Selayang, and Medan Tuntungan. The research method employed is quantitative with an operations research approach, through the stages of row reduction, column reduction, minimum zero coverage, and optimal assignment. The results show that the Hungarian Method produces an optimal assignment: K1 to Medan Selayang (IDR 390,000), K2 to Medan Tuntungan (IDR 380,000), K3 to Medan Kota (IDR 370,000), and K4 to Medan Baru (IDR 380,000), with a minimum total cost of IDR 1,520,000 per day. The savings obtained amount to IDR 40,000 per day or 2.56% compared to the initial assignment, equivalent to IDR 14,400,000 per year. This study demonstrates that the Hungarian Method is effectively applied to real-world assignment problems to enhance the efficiency of human resource allocation in the logistics sector.